Downregulation of miR‐98‐5p expression induces interleukin‐6 expression in rheumatoid fibroblast‐like synoviocytes. (21st June 2021) - Wang, Shujun; Geng, Qin; Zhang, Hongju; Du, Qing; Wei, Qiaofeng; Cui, Yanhui; Zhang, Xiuying; Yuan, Min
Abstract: Aim: The increased level of interleukin‐6 (IL‐6) plays a significant role in the pathogenesis of rheumatoid arthritis (RA). Specific blockade of IL‐6 or its receptor has been used successfully in treating RA. MicroRNAs can regulate gene expression and act as regulators of target genes. Manipulation of specific microRNAs provides a novel therapeutic strategy for treating/preventing diseases. This study explored the role of miR‐98‐5p in the regulation of IL‐6 expression in rheumatoid fibroblast‐like synoviocytes (RA‐FLSs). Methods: Real‐time PCR was used to detect miR‐98‐5p expression in RA‐FLSs and normal human fibroblast‐like synovial cells (HFLSs). Site‐directed gene mutagenesis and reporter gene assay were performed to identify the interaction between miR‐98‐5p and IL‐6. Manipulation of miR‐98‐5p expression in RA‐FLS used transfection with miR‐98‐5p mimic or inhibitor. Stimulation of FLSs with IL‐1β induced IL‐6 production. Enzyme‐linked immunosorbent assay was used to detect the level of IL‐6 secreted into the RA‐FLS culture supernatant. Results: Compared with HFLSs, the expression of miR‐98‐5p in RA‐FLSs was significantly downregulated, and was negatively correlated with DAS28 scores and rheumatoid factor. In patients with anti‐keratin antibody‐positive RA, the expression level of miR‐98‐5p was lower. miR‐98‐5p negatively regulated the expression of IL‐6 in RA‐FLSs. After IL‐1β stimulation, the expression of miR‐98‐5p decreased and the level of IL‐6 protein was upregulated during IL‐6 secretion. Conclusion: These data suggest that manipulation of miR‐98‐5p, which negatively modulates IL‐6 expression, may be a potential clinical approach in RA.